The Rise of Hindi OTT Platforms: Transforming India’s Entertainment Landscape - Geetam Shrivastava; Dr. A.Ram Pandey (Revista Electronica de Veterinaria, 2024)
The exponential growth of the Hindi Over-The-Top (OTT) platforms has fundamentally reshaped India’s entertainment industry by offering unprecedented accessibility and diversity in content consumption. Fueled by the digital revolution, these platforms have captured audiences across socioeconomic and geographical divides, introducing a paradigm shift from traditional broadcasting and cinema models to on-demand digital entertainment. geetam.media@gmail.com Furthermore, it examines opportunities for growth, particularly in terms of original content production, global expansion, and technological innovation. By highlighting case studies of notable productions, this study underscores the broader implications of Hindi OTT platforms for India’s entertainment industry and cultural fabric.